Diffusion Coefficient of Epoxy/ NBR/Bentonite tri- Composite in the Presence of Chemical Solutions - Raghad Hamid Hilal; Rafah Alwan Nassif (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Polymeric composite materials vary in their ability to allow chemical solutions and solvents to penetrate through them depending on the type and quantity of the reinforcement material and the immersion time in the chemical solution. This research included studying the diffusion property of an epoxy resin that is 80 % mixed with 20% nitrile rubber and reinforced with (1, 1.5, 3, 5%) bentonite by weight. The composite material was immersed in distilled water, diluted hydrochloric acid HCl (1:1), and sodium hydroxide NaOH at 5 M for eight weeks to determine the weight gain ratio and diffusion coefficient. The results showed that the weight gain values increased with an increase in the immersion time, but they decreased with the increase in the amount of bentonite at the same immersion time, so the diffusion coefficient was reduced with an increase of bentonite. SEM images show the surface morphology of the composite material